2016
DOI: 10.1113/ep085323
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of rapid eye movement sleep during adolescence increases energy gain and metabolic efficiency in young adult rats

Abstract: New Findings r What is the central question of this study?Sleep curtailment in infancy and adolescence may lead to long-term risk for obesity, but the mechanisms involved have not yet been determined. This study examined the immediate and long-term metabolic effects produced by sleep restriction in young rats. r What is the main finding and its importance?Prolonged sleep restriction reduced weight gain (body fat stores) in young animals. After prolonged recovery, sleep-restricted rats tended to save more energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
3
6
1
Order By: Relevance
“…Control animals were placed in the same containers but the disk was rotating over sawdust rather than water. During the month of recovery following the intervention, rats who were previously sleep restricted showed greater body weight gain and energy stores and decreased energy expenditure as compared to controls, despite eating the same amount [11]**.…”
Section: Introductionmentioning
confidence: 99%
“…Control animals were placed in the same containers but the disk was rotating over sawdust rather than water. During the month of recovery following the intervention, rats who were previously sleep restricted showed greater body weight gain and energy stores and decreased energy expenditure as compared to controls, despite eating the same amount [11]**.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of body weight gain in sleep restricted/deprived animals is a widely described phenomenon that occurs with any technique employed to induce sleep loss (Barf et al., 2012; Everson & Wehr, 1993; Hipolide et al., 2006; Koban & Swinson, 2005; Koban et al., 2008; Moraes et al., 2014; Suchecki et al., 2003; Venancio & Suchecki, 2015). Recent studies conducted in our laboratory showed that young rats subjected to REM sleep restriction for 21 days had lower body weight gain (Ribeiro‐Silva et al., 2016) and smaller growth rate (naso‐anal length measurement) compared to control rats (da Silva Rocha‐Lopes et al., 2018). Corroborating the literature data, our results showed a reduction in body weight gain of approximately 64%, 34% and 35% in the SR groups compared to controls after 7, 14 and 21 days, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Regardless of the sleep restriction method used, e.g. gentle handling (Jha et al., 2016), forced activity (Barf, Meerlo, & Scheurink, 2010; Sengupta et al., 2017), a single‐platform method (Ribeiro‐Silva, Nejm, da Silva, Suchecki, & Luz, 2016; Venancio and Suchecki, 2015) or a modified multiple‐platform method (da Silva Rocha‐Lopes, Machado, & Suchecki, 2018), the result consistently involves metabolic changes. Importantly, these different methods result in disruption of both non‐REM and REM sleep phases, indicating that both are critical for energetic metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study provides the present study with foundational evidence of memory deficits as a result of adolescent CSR. Their findings speak to the vulnerability of the adolescent brain, as do a number of other studies in which sleep disturbances in adolescence show immediate and, in some cases, long-lasting changes(Billeh et al, 2016; Novati et al, 2011;Saré et al, 2016;Ribeiro-Silva et al, 2016). The demonstrated vulnerability of the adolescent brain to sleep deficiency and the gap in research on resulting cognitive…”
mentioning
confidence: 76%